POLA INTERAKSI SOSIAL SESAMA LANJUT USIA KORBAN PENELANTARAN DI PANTI SOSIAL TRESNA WERDHA LASWI BANDUNG - Illian, Deo Rizal Miftakhul; Andayani, Rini Hartini Rinda; Ardiyantika, Sulistyary (Politeknik Kesejahteraan Sosial Bandung, 2025)
This study aims to obtain an empirical picture of the interaction patterns of fellow elderly victims of neglect at the Tresna Werdha Laswi Bandung Social Institution which includes: (1) informant character; (2) elderly social contact; (3) elderly communication (4) elderly social interaction patterns. This research uses a qualitative approach with a descriptive method. The informants in this study are 4 people, including 3 PPKS, elderly abandoned and 1 caregiver with the determination of informants using purposive sampling. The data collection techniques used are in-depth interviews, observations and documentation studies. The results of the study show that in the pattern of social interaction, some elderly people in PSTW Laswi have been able to adapt to a new environment so that they are able to interact with other elderly but there are also those who have not been able to adapt well to the new environment which makes their social interaction disrupted. Based on this, the researcher proposed a program, namely